Are Modern Bloggers Following in the Footsteps of Publius? (And Other Musings on Blogging by Legal Scholars . . .) - Gail Heriot (Washington University Law Review, 2006)
Is legal blogging an antidote to the hyper-scholasticism that sometimes characterizes the legal academy today? Or is it a self-indulgence for legal scholars? It's hard to know. On the one hand, there is a proud American tradition behind the publication of concise but erudite essays aimed at a broad audience concerning the important legal issues of the day, starting with the Federalist Papers. It's hard to believe that neglecting that tradition in favor of a cloistered academic existence in which legal scholars write only for each other could be a good thing. On the other hand, even the best legal blogs contain more chaff than wheat. And legal bloggers who offer mostly ill-considered opinions on every topic imaginable may bring disrepute to the legal academy. On the whole, I am inclined to be cautiously optimistic about the potential value of legal blogging. But then I enjoy blogging, so perhaps my judgment on these matters ought not be deferred to too readily.
Keywords: Blogs; Law -- Study & teaching; Legal literature; United States